Manifestation Of Moral And Ideological Threat In Preschool Children (Eurasian Scientific Herald, 2024)
This article includes itself directions and sentences on deferent types of socio-culturalspiritual, ideological menace and reference on preventive measures or precautions for nursery age of children.